Egyptian media policies to protect minors from harmful content and promote positive media use - Abu-Seada, Nour Hussien (AUC Knowledge Fountain, 2019)
Children are by far the most important asset for the future of any nation. Hence, any investment in them will not only reflect positively or negatively on their homeland and society, but maybe even the whole world. With the understanding that early childhood is an extremely important and critical stage for mental, physical and psychological development, it is highly important to constantly provide a healthy environment for young children in order to nourish those seeds that will harvest the future. Media is on the forefront means influencing peoples lives nowadays, some even consider it a source of information. Children, being easily influenced by their surrounding environment, are at greater risk mainly due to the ability of Television and media content to affect their development, behavior and entire life, which can either build or break them. Several developed countries have figured out the enormous influence media can have on audience both positively and negatively, especially on the most vulnerable audience like “children”. With that in consideration, many countries have taken sufficient measures to ensure the protection of minors from being subjected to any harmful media content, or content that might not be generally suitable for their age. In addition, promote more developmental media content as an alternative for children. Unfortunately, that is not the case in most developing countries such as Egypt. Children represent around 40% of the total Egyptian population. Basic research results suggest that many Egyptian children engage in around 3 to 4 hours of media content daily. This is around 21 hours weekly, 90 hours monthly, and 1095 hours yearly (which is almost one month and half of each year of their lives continuously). That’s only the minimum basic figures, since many parents highlight that their children’s television viewership increases dramatically on weekends, holidays, and vacations! Noting that this is not just some fun entertainment time, but rather it’s thoughts, ideas, beliefs, attitudes, and behaviors being absorbed by the child, becoming a huge influence on their mental, physical and psychological development, and affecting their entire life! Furthermore, research results also indicate the high need and demand for media regulations to protect children from harmful media and encourage high standard production of more positive alternatives, specially designed for Egyptian Children serving their needs and interests at different age groups. This research consists of: I) Literature review, providing the following: • General understanding of the mental, physical and psychological developments of a child • Positive and negative impacts of media on children’s development and behavior • Overview on international policies in different countries in regard to children and media • Understanding the situation in Egypt: • A brief overview on the History of Child programming and policies II) In-depth interviews with: A. 10 Parents from different age groups, social classes and educational background: This provided a better understanding of what Egyptian children watch, reasons behind their preference, how it affects them, parent’s concerns, what is needed, etc. B. A panel of 3 Child expert’s including: 1. DR. MAHA EMAD EL DIN TEENAGE PSYCHIATRY CONSULTANT ASSISTANT PROFESSOR AND HEAD OF PSYCHIATRY DEPARTMENT BANI SWEIF UNIVERSITY 2. Dr. SAHAR DAWOOD CHILD PSYCHIATRIST PHD IN CHILD MENTAL HEALTH 3. MARIAM MEDHAT FOUNDER OF PARENTING FORMULA PARENTING COUCH Child experts provided their opinion on current media content available for children to watch and its possible impact on their physical, psychological, and metal health, positively or negatively. In addition to validating and confirming information provided in the literature review. C. MEDIA EXPERTS: 1. NAELA FAROUK Head of National Egyptian Broadcast, Maspiro 2. NADIA MABROUK Head of Radio Networks, Maspiro 3. MAGDY LASHEEN Advisor of the President of the National Information Authority 4. HISHAM SILIMAN Head of DMC Network Owner of Hama Film Production 5. ABDELLATIF EL MENAWY CEO and Editor in Chief, Al Masry Al Youm 6. ALBERT SHAFIK Extra News Channel Director 7. MARIAM NAOUM Egyptian Drama Author/Writer 8. SANAA MANSOUR Egyptian TV Presenter 9. GALAL AWARA Deputy of Culture and Information Committee The House of Representatives Former TV Presenter D. MEDIA ACADEMICS: 1. DR. RASHA ALLAM Assistant Professor and Associate Chair Journalism and Mass Communication Department, AUC 2 DR. HOWAIDA MOUSTAFA Head of Radio and Television Department Mass Communication Department, Cairo University 3. DR. MONA EL HADIDI Mass Communication Professor Mass Communication Department, Cairo University 4. DR. HANAA MAREAY Assistant Professor Mass Communication Department, MSA E. NGO: 1. OLFA G. TANTAWI Communication for Development Officer, UNICEF Egypt These interviews discuss various issues regarding current media content, highlighting the need for Egyptian media regulation to protect minors and provide more positive media content alternatives. III) Brief Research findings: There is a common dissatisfaction with current media content provided. Main concerns include: Violence both verbal and physical, use of bad language, inappropriate scenes, and other matters in local and foreign content that are culturally not expectable in Egypt. In addition, there is high need and demand for media regulation. In order for such regulation to be precise and efficient, it is recommended to include a panel of advisory experts representing media professionals as well as child experts in the policy setting process. V) Suggested Policies to: A. Protect children from harmful media content. B. Promote positive media use and encourage the production of high quality local Egyptian child programming targeting different age groups.